Chinese Approach Research Hotspots and Content Analysis of Taijiquan Health Interventions - Zhang, Peng; Luo, Qingyuan; Liu, Mingyu (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Objective: Taijiquan, as a representative of China's indigenous traditional sports, embodies the profound cultural and philosophical heritage of the Chinese nation and is an integral part of Chinese martial arts. In recent years, Taijiquan has garnered significant attention in the medical field, both domestically and internationally, due to its notable benefits in disease prevention, health protection, excellent safety profile, and affordability for exercise. It has gained widespread popularity and development globally. This development owes much to scientific research exploring the health-promoting functions of Taijiquan. Current studies have indicated that Taijiquan offers substantial health benefits, including enhanced muscle strength, improved balance and control, stress reduction, as well as its involvement in the prevention, treatment, and rehabilitation of various diseases. These diseases encompass a wide range, such as osteoarthritis, hypertension, diabetes, coronary heart disease, and more, where Taijiquan has demonstrated significant therapeutic effects. As a distinguished representative of China's indigenous traditional sports, it is imperative to review the significant research achievements of Chinese scholars in the field of clinical intervention with Taijiquan. A thorough analysis of their research topics and study designs is essential. This effort aims to provide insights and references for the scientific development and standardization of Taijiquan health interventions in China. Ultimately, it is in line with the implementation of the "Taijiquan Health Project" and the "Healthy China" strategy to better serve the health and well-being of the population.Methods: To enhance the reliability and persuasiveness of the data, this study conducted a comprehensive search using the Web of Science TM Core Collection database and the China National Knowledge Infrastructure (CNKI) for all clinical experimental research papers on Taijiquan health interventions published by Chinese scholars (with the first author affiliated with Chinese institutions) since the establishment of our database. The search and download were conducted up to June 30, 2023. A total of 595 papers were retrieved, and after full-text assessment based on inclusion and exclusion criteria, 258 papers were ultimately included. Basic information from the included papers was extracted, including publication date, authors, institutions, journals, the health promotion or disease conditions of the study subjects, types of interventions for medical conditions, research design information such as sample size, basic characteristics of participants (gender, age, etc.), randomization, blinding, control interventions, Taijiquan exercise details (style, duration, frequency, intensity), outcome measures, experimental results, and conclusions. Statistical analysis was performed on these data.Results: The number of papers included in this study indicates a significant growth trend in the research conducted by Chinese scholars in the field of Taijiquan health interventions. These studies have been primarily published in core journals related to geriatrics, rehabilitation medicine, and sports medicine. This highlights the continuous academic interest in Taijiquan research and widespread recognition of its clinical application potential. In terms of author and institutional distribution, scholars from Hong Kong and institutions like the Shanghai University of Sport have shown significant research activity and strength in the field of Taijiquan health interventions, driving its development and progress and making important contributions to Taijiquan health intervention research. Regarding the subjects of the included studies, Taijiquan has garnered widespread interest among Chinese scholars in research related to mental, behavioral, or neurodevelopmental disorders, circulatory system diseases, musculoskeletal disorders, or connective tissue diseases. These topics have become prominent and highly regarded in Taijiquan health intervention research, providing extensive and in-depth research directions. In terms of experimental design, researchers often use Taijiquan as the sole therapeutic intervention in the experimental group or combine it with other intervention methods to evaluate its superiority compared to other treatment modalities. This experimental design allows us to comprehensively understand the effectiveness of Taijiquan in different therapeutic contexts. In selecting intervention protocols, Yang-style Taijiquan is usually given priority, especially the simplified and easy-to-learn Yang-style 24-form Taijiquan routine, which has been widely adopted. Currently, Taijiquan intervention measures exhibit a variety of complexities, with significant differences in the design of treatment frequency, duration, and intervention duration among each study. The current research results indicate that Taijiquan interventions are most commonly administered 3-4 times a week, with each session lasting 31-60 minutes, and the intervention period generally does not exceed 12 weeks. In research reports, only a minority provided detailed procedures and specific schedule plans for the interventions, information on whether participants received adequate training, and qualifications of the instructors. A few studies offered detailed descriptions of the specific Taijiquan exercise protocols and the grading system for Taijiquan. It is not feasible for participants and instructors to be blinded in Taijiquan exercise studies, but to reduce bias, outcome assessors and analysts were blinded. However, only a minority of the studies reported the use of blinding procedures. Some studies conducted follow-ups with participants, which included exercise reminders, supervision, and guidance. Participants were not required to record their daily exercise, including the type, exercise duration, and frequency, which could potentially introduce confounding factors affecting the results. Additionally, there was no supervision during the follow-up period, which might have amplified the impact of participants' self-initiated exercise. Although Taijiquan interventions for health have shown a rich clinical research foundation in existing studies. However, as an exercise prescription that serves as a complementary alternative medical intervention, Taijiquan health benefits, despite being validated in clinical intervention research, have not yet formed a standardized exercise rehabilitation program for inclusion in global exercise guidelines due to an overall lack of robust clinical evidence, such as insufficient sample sizes, participant heterogeneity, and outcome measures. Therefore, in conducting such clinical trials, researchers must be acutely aware of the unique nature of Taijiquan as a traditional mind-body exercise and provide detailed descriptions of the intervention characteristics. Future clinical trials should also strive to minimize potential sources of bias, including ensuring adequate randomization procedures, blinding during outcome assessments, and reporting safety-related information, in order to reduce heterogeneity resulting from methodological issues. This will contribute to a deeper understanding of the efficacy, safety, and mechanisms of Taijiquan in health interventions and provide it with more scientific evidence.Conclusion: The study reveals that in recent years, Chinese scholars have shown an overall increasing trend in research on Taijiquan health interventions, with the majority of studies reporting positive outcomes. However, due to the diverse range of research types, participants, Taijiquan interventions, and reported outcomes, along with disparities in research quality, there is an urgent need for more rigorous scheme designs, process evaluations, and result verifications to establish standardized Chinese guidelines for Taijiquan-based health interventions. Furthermore, further research and comprehensive assessments are imperative to explore the potential benefits of Taijiquan thoroughly.